Oenological Characteristics of Four Non-Saccharomyces Yeast Strains With β-Glycosidase Activity - Qin, Tao; Liao, Jing; Zheng, Yingyuan; Zhang, Wenxia; Zhang, Xiuyan (Frontiers in Microbiology, 2021)
Non-Saccharomyces yeast with β-glucosidase activity might positively contribute to the flavor and quality of wines. The contribution of four non-Saccharomyces yeast strains Issatchenkia terricola SLY-4, Pichia kudriavzevii F2-24, P. kudriavzevii F2-16, and Metschnikowia pulcherrima HX-13 with β-glucosidase activity to the flavor and quality of wine making was studied. Compared with those of S. cerevisiae single fermentation, the four non-Saccharomyces yeast strains could grow and consume sugar completely with longer fermentation periods, and with no significantly negative effect on chemical characteristics of wines. Moreover, they produced lower content of C6 compounds, benzene derivative, and fatty acid ethyl ester compounds and higher content of terpene, β-ionone, higher alcohol, and acetate compounds. Different yeast strains produced different aroma compounds profiles. In general, the sensory evaluation score of adding non-Saccharomyces yeast-fermented wine was better than that of S. cerevisiae, and I. terricola SLY-4 fermentation received the highest one, followed by P. kudriavzevii F2-24, P. kudriavzevii F2-16, and M. pulcherrima HX-13 from high to low. The research results provide a theoretical basis for the breeding of non-Saccharomyces yeast and its application in wine making.